New insights into high-temperature deformation and phase transformation mechanisms of lamellar structures in high Nb-containing TiAl alloys. (March 2020) - Song, Lin; Appel, Fritz; Wang, Li; Oehring, Michael; Hu, Xingguo; Stark, Andreas; He, Junyang; Lorenz, Uwe; Zhang, Tiebang; Lin, Junpin; Pyczak, Florian
Abstract: The paper describes the microstructure evolution by high-temperature compression of a high Nb-containing TiAl alloy. The paper extends a previous publication [Song, et al. Intermetallics 109 (2019) 91–96], in which a unique twin-like morphology in the α2 (Ti3 Al) phase was reported. However, the origin of these structures could not be clarified without doubt. The present study is focused on phase transformations that in this multiphase alloy can be associated with deformation. Particular attention is paid to local transformations of the α2 phase into O phase or ω-related phases, which, because of structural and chemical similarity of these phases with α2, can easily occur and could mistakenly be considered as a twin structure. The details of the atomic processes involved are elucidated by electron microscopy. Given the large shufflings and the atomic site interchanges required for the operation of this twinning system, it is concluded that twinning of the α2 phase is a diffusive-displacive process. Within the α2 phase, ωo is heterogeneously nucleated. The nucleation sites are defect-rich areas, which are subjected to high local stresses. The study strongly emphasizes the close relationship between high-temperature deformation and phase transformations in multiphase titanium aluminide alloys. Graphical abstract: Image, graphical abstract